Diffusion and Adsorption of Copper Ion in HPMC-modified Bentonite - WANG Bao, HU Ye-hao, ZHU Jia-jia, ZHANG Di, ZHOU Hao-ran (长江科学院院报)
A series of through-diffusion tests were carried out to explore the diffusion and adsorption behaviors of Cu2+ in bentonites modified with hydroxypropyl methylcellulose (HPMC). The test results were compared with those of untreated bentonite. Pollute V7.0 was employed to quantitatively evaluate the impact of HPMC on the performance of bentonite in intercepting Cu2+. The diffusion test results indicated that when the HPMC content reached 2% and 5%, the capacity of bentonite adsorbing Cu2+ decreased by 40% and 46%, respectively, while the diffusion coefficient of Cu2+ dropped by 7% and 34%, correspondingly. The results from Pollute V7.0 demonstrated that adding 2% and 5% HPMC to sodium bentonite enhanced the performance of bentonite for adsorbing Cu2+ by factors of 1.34 and 2.03, respectively. Overall, the findings of this study offer valuable information for assessing the performance of HPMC-modified bentonite.